2016
DOI: 10.29252/ijrm.14.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sexual dysfunction in women with infertility and without infertility referred to Al-Zahra Hospital in 2013-2014

Abstract: Background:One of the affected aspects in infertile women that have not been given sufficient attention is sexual function. Sexual function is a key factor in physical and marital health, and sexual dysfunction could significantly lower the quality of life. Aim of this study was to assess the comparison sexual dysfunction in women with infertility and without infertility, admitted to Al- Zahra Hospital.Objective:We decided to assess the prevalence of women sexual disorders in fertile and infertile subjects, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
2
17
1
2
Order By: Relevance
“…All cases filled FSFI form. They found significant difference between desire, arousal, satisfaction and total sexual dysfunction in both groups, but they could not find significant difference in lubrication, orgasm and pain (Mirblouk et al., ). We found similar results in our cohort.…”
Section: Discussionmentioning
confidence: 97%
“…All cases filled FSFI form. They found significant difference between desire, arousal, satisfaction and total sexual dysfunction in both groups, but they could not find significant difference in lubrication, orgasm and pain (Mirblouk et al., ). We found similar results in our cohort.…”
Section: Discussionmentioning
confidence: 97%
“…Khademi, et al found that the prevalence of erectile dysfunction (ED) was higher in men with infertility than in the normal population regardless of any degree of ED [9]. With regard to females, many previous studies have also found that the prevalence of female sexual dysfunction (FSD) was higher in infertile women than women with normal fertility [5,[10][11][12]. A diverse variety of risk factors may have a negative influence on the impaired qualities of sexual function in women with infertility, such as the female's age, educational level, duration of infertility and assisted reproduction treatment etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital Anxiety and Depression Scale (HADS) is designed to measure mood swings, especially anxiety and depression. On this scale, there are seven questions about anxiety symptoms (questions 1,4,5,8,9,12) and there are seven questions about the symptoms of depression (questions 2, 3,6,7,10,11,14). It is graded on the basis of a four-point scale (0, 1, 2, 3) (0 = never, 1 = seldom, 2 = sometimes & 3 = always).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Sexual problems are common in infertile couples and have been reported between 5% and 55% [5]. One of the factors impressed in infertile women is a sexual function (SF), which is a key factor in physical and marital health and can signi cantly reduce the quality of life [6].…”
Section: Introductionmentioning
confidence: 99%